Optimization of starch isolation from red sorghum using response surface methodology. (May 2018) - Qi, Yuting; Du, Fangling; Jiang, Zhuqing; Qiu, Bin; Guan, Qianqian; Liu, Jie; Xu, Tongcheng
Abstract: A Wet-milling process for isolation of starch from red sorghum grains was optimized in this paper. A method combining a Plackett-Burman design (PBD), the steepest ascent method, and a Box-Behnken design (BBD) was used to evaluate the effects of major treatment process variables, including the soaking solid-liquid ratio, NaOH concentration, soaking temperature, soaking time, stirring rate, ultrasonic power, milling solid-liquid ratio, milling time and milling rate, on the starch isolation. The response value was a composite value (that is, the sum) of starch yield and sorghum peeling rate. Soaking temperature, soaking time and milling time were significant factors. The conditions of adjusting the temperature of soaking to 50 °C, soaking time to 36 min and milling time to 8 min and 10 s would favor maximum response value obtainment. A mathematical model with high determination coefficient (R 2  = 0.9825) was developed and showed good consistency between the experimental values (149.26%) and predicted values (148.87%), which indicated the suitability of the developed model. Starch with high yield (54.58%) and satisfactory color was obtained from red sorghum after optimization. Highlights: Optimization study based on starch yield and sorghum peeling rate was conducted. Soaking temperature, soaking time and milling time influenced starch isolation. Starch with high yield was isolated from red sorghum by optimization. The peeling improved the color of the isolated starch.